Anti-CD20 monoclonal antibodies in chronic lymphocytic leukemia: from uncertainties to promises. (May 2016) - Bagacean, Cristina; Zdrenghea, Mihnea; Tempescul, Adrian; Cristea, Victor; Renaudineau, Yves
Over the last two decades, anti-CD20 monoclonal antibody (mAb) therapy has improved patient outcome in B-cell malignancies, and confirmed CD20 as an important target in chronic lymphocytic leukemia (CLL). Until recently, the gold standard was based on the utilization of rituximab combined with chemotherapy (fludarabine and cyclophosphamide), but patients often relapse. Next, with our better understanding of mAb engineering, anti-CD20 mAb therapy has evolved with the development of new mAb permitting significant clinical responses by improving pharmacokinetics, safety, activity and immunogenicity. Last but not least, the development of key tumoral tyrosine kinase inhibitors and their association with anti-CD20 mAb is a work in progress with promising results.